Tenacious, sad account of NZ complicity on East Timor - Matt Mollgaard (Asia Pacific Network, 2007)
This is an essential book for any one interested in the way that New Zealand formulates and carries out its foreign policy. It is also a stark reminder that New Zealand, a founder member of the United Nations, a vocal supporter of decolonisation and a country much-praised for its peacekeeping efforts all over the world has not always been willing to take a moral stance when balancing trade, security and human rights. Maire Leadbeater has produced the most detailed account so far of New Zealand's involvement in the tragedy that engulfed East Timor during and after the 1975 Indonesian invasion of the former Portuguese colony.